Food Insecurity and Hunger among Internally Displaced Families in Benghazi, Libya - El-Mogassabi, Abeir; Saad, Salima; El-Mani, Souad; Alhaaj Ali, Ali; Alshatshat, Ayman; El Brki, Mahmod (Libyan Journal of Public Health Practices, 2025)
Food security (FS) is a critical issue exacerbated by conflict and pandemics. This study investigated FS among internally displaced persons (IDPs) in Benghazi, Libya, during the COVID-19 pandemic. A cross-sectional survey was conducted with 120 IDP families residing in three camps in Benghazi, Libya. The Radimer/Cornell Hunger Scale was used to assess household FS. The findings revealed a high prevalence of food insecurity, with 91.7% of families experiencing some level of food insecurity. Factors such as parental education, paternal employment, and access to food storage and preparation equipment significantly influenced FS levels. The study highlighted disparities in FS between camps, with El-Helis camp showing higher levels of food insecurity. The complex interplay of conflict and pandemic-related disruptions to food systems, employment, and financial stability contributed to these challenges. This research emphasizes the urgent need for targeted interventions to address food insecurity among IDPs in conflict-affected regions. Such interventions should include immediate food assistance, improved distribution systems, and long-term strategies for building self-sufficiency and enhancing access to food resources